Consumer approach of health and ayurveda - Szabó, Sára; Szente, Viktória; Szakály, Zoltán; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2014)
The aim of this study was to explore the differences of health interpretation between people with ayurvedic approach and non ayurvedic but health conscious approach. While Ayurveda has a holistic approach to health, the European medicine focuses on its physical aspects (bio-medicinal model). Although theoretically a complex interpretation of health (bio-psycho-social model) is the most accepted in Hungary, we examined whether it prevails on a practical level. We carried out a representative survey (N=1000) to examine the health-related knowledge and behaviour of the Hungarian population. To achieve deeper understanding of the subject, we carried out two focus group discussions. We selected health conscious people in the first group and ayurvedic oriented people in the second group to compare their attitudes towards health. The results showed that the majority of the Hungarian population (83,2%) have recognised that health is more than a bio-medicinal approach, it is built up of physical, psychological, mental and social factors, but in most cases we found huge gaps between recognition and action. During discussions the ayurvedic oriented group construed an interpretation that contained all the five health dimensions of WHO and mentioned spirituality as an additional dimension, while the health conscious group mainly emphasized physical health. We also asked the participants about their own health behaviour and found the same pattern. It can be stated that the Hungarian population theoretically admits an integrative model of health but it does not appear in their health behaviour. It seems that ayurvedic orientation contributes to bringing knowledge to practice. Ayurvedic oriented people have a more complex interpretation of health and are willing to do more for their health, so they are a good target group for prevention campaigns and health care services. It also suggests that the spread of ayurvedic approach could contribute to better health behaviour in Hungary.